Kitab kuning’s existence in the history of Islamic education and its relevance to modern Islamic society in Aceh - Inayatillah, Inayatillah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
This study aims to explain the role of kitab kuning (classic Islamic books) in the treasures of Islamic religious education in Indonesia, so that it can be seen as one of the many influential aspects in the formation of educational discourse in Indonesia. It is carried out in a qualitative descriptive method that is directed to see the scientific discourse of Islamic education and the history of education. Data collections were carried out through literature studies employing historical approach to understand the historical context, changes, or evolution of thoughts or concepts as well as a comparative observation. The data obtained formed an analysis of traditional education discourse, its relevance in history and how the position of kitab kuning in modern education these days. The result of study shows that modern Islamic education today seems unable to abandon kitab kuning as a basic methodology in understanding Islam. There is a phenomenon of increasingly inclusive study of the new format of digitized kitab kuning, not only in pesantren but also in universities. This leads to the synthesis that kitab kuning is potential to be a general learning particularly with the increasingly open dissemination of Islamic literacy.  The results of the present study are expected to be able to contribute to the education and teaching system.